The Greek-Cypriot Dialect in Writing: Orthographic Conventions and Typographic Practices. - Papadima, Aspasia; Ayiomamitou, Ioli; Kyriacou, Stelios (My University, 2011)
This paper investigates issues related to the interplay of typography and orthography design for a non-codified dialect. Specifically, it deals with the orthographic representation of the nonstandard, Greek-Cypriot dialect (henceforth GC) spoken by the Greek-Cypriots in Cyprus with a focus on the unconventional and highly controversial orthography of the distinctive phonological features of the GC dialect, all representing consonantal variation (Schneider & Wagner, 2006) . The analysis and interpretation of the study’s findings revealed that traditionally the representation of the GC dialect in written discourse has been characterized by non-systematicity. In most cases the choice of spelling conventions has been underpinned by contradictory language ideologies regarding the different types of orthographic systems (Sebba, 2007) . As Halliday stated, language has a semiotic value, through language we construct to a great extent our identities, our ideologies and experiences. In the case of Cyprus, language has indeed obtained the central and almost exclusive role in indexing the national and cultural identity of GCs (Goutsos & Karyolemou, 2004) . In addition, the study shows that a general confusion regarding the “correct” orthography of the dialect prevails, raising numerous debates among linguists and lexicographers.
Keywords: Typography; Orthography; Greek-Cypriot dialect